Impact of automation and cals technologies on human factor in production - Hubar, A. Y.; Sotnik, S. V. (My University, 2024)
The study examines the impact of automation and CALS-technologies on the human factor in production across various industries. It highlights the varying degrees of influence these technologies have, particularly in the automotive (40%), aviation (35%), and electronics (30%) sectors. The research underscores how CALS-technologies enhance communication, reduce errors, and improve product quality, while also noting the importance of continuous worker training and development. A strategy is proposed to support workers in adapting to these new technologies through customized training programs, mentoring, online courses, and hands-on training. This study provides valuable insights into the complex effects of CALS-technologies on the human factor in production and stresses the need for a balanced approach that considers both technological and social dimensions. The findings can serve as a foundation for further research into optimizing the implementation processes of CALS-technologies in various production sectors. This research has addressed the problem of how automation and CALS-technologies affect the human factor in production. The study analyzed key aspects of this influence across different industries and identified the varying impacts of CALS-technologies, with the most significant effects observed in the automotive, aviation, and electronics sectors. The work also outlined the benefits of these technologies, such as improved communication, error reduction, and enhanced product quality, while acknowledging the need for ongoing training and development for workers. Additionally, a comprehensive strategy was proposed to facilitate worker adaptation to new technologies, including tailored training programs, mentoring, online courses, and practical training sessions. This work contributes to a deeper understanding of the multifaceted impact of CALS-technologies on human factors in production and emphasizes the importance of a balanced approach to their implementation.
Keywords: CALS technologies; human factor